Synthesis of imidazo[2,1-b]thiazoles linked to an unprotected carbohydrate moiety - Barradas, Jose Sebastian (2012)
Two series of imidazo[2,1-b]thiazoles substituted on C-3 or C-5 with an unprotected carbohydrate moiety were synthesized. Different protective groups for position 3 of the carbohydrate moiety were tested (acetyl, tert-butyldimethylsilyl (TBDMS), and p-methoxybenzyl (PMB)) and the latter turn out to be the best strategy to obtain the desired products. Full deprotection of the carbohydrate was performed successfully in only one step.